Extracellular Vesicles in Trypanosomatids: Host Cell Communication - Torrecilhas, Ana Claudia; Soares, Rodrigo Pedro; Schenkman, Sergio; Fernández-Prada, Christopher; Olivier, Martin (Frontiers in Cellular and Infection Microbiology, 2020)
Trypanosoma cruzi, Trypanosoma brucei and Leishmania (Trypanosomatidae: Kinetoplastida) are parasitic protozoan causing Chagas disease, African Trypanosomiasis and Leishmaniases worldwide. They are vector borne diseases transmitted by triatomine bugs, Tsetse fly and sand flies, respectively. Those diseases cause enormous economic losses and morbidity affecting not only rural and poverty areas but are also spreading to urban areas. . During the parasite-host interaction, those organisms release extracellular vesicles (EVs) that are crucial for the immunomodulatory events triggered by the parasites. EVs are involved in cell-cell communication and can act as important pro-inflammatory mediators. Therefore, interface between EVs and host immune responses are crucial for the immunopathological events that those diseases exhibit. Additionally, EVs from these organisms have a role in the invertebrate hosts digestive tracts prior to parasite transmission. This review summarizes the available data on how EVs from those medically important trypanosomatids affect their interaction with vertebrate and invertebrate hosts.